2017
DOI: 10.1016/j.scitotenv.2017.06.178
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in wheat productivity and soil quality can accomplish by co-application of biochars and chemical fertilizers

Abstract: The beneficial role of biochar is evident in most of infertile soils, however this is argued that increment in crop yield owing to biochar application does not always achieve in cultivated/fertile soils. The nutrient biochar believed to enhance crop yield and soil fertility than structural biochar that may offset the positive effect of chemical fertilizer on crop performance but improves soil structural properties. Therefore, we investigated the effect of biochars [produced from nutrient rich feedstocks like p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 46 publications
7
55
0
Order By: Relevance
“…Similar results were reported by Mete et al [27], Lima et al [68], Sadaf et al [47] where NPK treatments gave higher maize biomass and soybean yield, compared to biochar or biochar in combination with NPK. In a recent study, in [61] an increase in yield and N uptake in rain-fed rice yield in two contrasting soils was reported, following the application of rice husk biochar combined with chemical NPK.…”
Section: Effect On Biomass Yieldsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results were reported by Mete et al [27], Lima et al [68], Sadaf et al [47] where NPK treatments gave higher maize biomass and soybean yield, compared to biochar or biochar in combination with NPK. In a recent study, in [61] an increase in yield and N uptake in rain-fed rice yield in two contrasting soils was reported, following the application of rice husk biochar combined with chemical NPK.…”
Section: Effect On Biomass Yieldsupporting
confidence: 89%
“…Finally, the macro nutrient (Ca, Mg, Mn, and Na) and heavy metal (Cr, As, Fe, Zn, and Cu) uptake was calculated by multiplying the total dry biomass weight by the individual ion content [46]. Apparent nutrient recovery (ANR) from all treatments was calculated according to Sadaf et al [47] using Equation 1:…”
Section: Plant Tissue Analysismentioning
confidence: 99%
“…This was reasonable because it was demonstrated that land degradation would have a great negative inuence on the food security and crop yields worldwide. 45 The reasons causing land degradation were various, including growing exhaustive crops, using too much chemical fertilizers and using improper agriculture practices. 46,47 Biochar had some good characteristics, including being rich in nutrients, improving the nutrient utilization efficiency of crops, adjusting soil pH and removal of soil pollutants, etc.…”
Section: Title Analysismentioning
confidence: 99%
“…At the same time, effective applications are questionable, as farmers need to combine biochar application with sustainable fertilizers and water input [5]. Biochar efficacy on yield increase was attributed to the application of the material in unfertile/barren lands, rather than to fertile soils [12] and the biochar co-application with fertilizers has been suggested [13].…”
Section: Introductionmentioning
confidence: 99%